Promoting Compliance in Children Referred to Child Protective Services: A Randomized Clinical Trial. Issue 2 (28th February 2019) - Lind, Teresa; Bernard, Kristin; Yarger, Heather A.; Dozier, Mary
Abstract : Early experiences of maltreatment have long‐term negative effects on children's compliance. This randomized clinical trial examined whether a brief preventative intervention (Attachment and Biobehavioral Catch‐up; ABC) was effective in enhancing compliance in children who had been referred to Child Protective Services. Participants included 101 parent–child dyads who received either ABC or a control intervention when children were infants ( M = 9.4 months old, SD = 6.1). When children were approximately 36 months old ( M = 38.5, SD = 3.0), ABC children demonstrated significantly better compliance than control children. Further, parent sensitivity, measured 1 month post intervention when children were, on average, 18.4 months old ( SD = 6.9) partially mediated the effect of ABC on child compliance at 36 months old.